Self‐Powered Nanoscale Photodetectors - Tian, Wei; Wang, Yidan; Chen, Liang; Li, Liang (Small (Weinheim an der Bergstrasse, Germany), 2017)
Novel self‐powered nanoscale photodetectors that can work without an external power source, which have great application potential in next‐generation nanodevices that operate wirelessly and independently, are being widely studied. This review aims to give a comprehensive summary of the state‐of‐the‐art research results on self‐powered nanoscale photodetectors. An introduction of recent progress on Schottky junction photodetectors is provided. Two types of Schottky junctions are discussed in detail: metal–semiconductor and semiconductor–graphene junctions. Next, recent developments of p–n junction photodetectors are highlighted, including homojunction and heterojunction photodetectors. Then, piezo‐phototronic effect enhanced photodetection performances of Schottky junctions and p–n junctions are discussed. Then, significant results on the photoelectrochemical‐cell‐based photodetector and integrated self‐powered nanosystem are presented, followed by a systematic comparison of different types of photodetectors. Finally, a summary of the previous results is given, and the major challenges that need to be addressed in the future are outlined. The hope is that this review can provide valuable insights into the current status of self‐powered photodetectors and spur new structure and device designs to further enhance photodetection performance. Self‐powered nanoscale photodetectors that work without an external power source and meet the demands of small size, low weight, and low power consumption are being widely studied for next generation nanodevices. Here, a comprehensive summary is given of the state‐of‐the‐art results on self‐powered nanoscale photodetectors, including those based on the Schottky junction, p–n junction, photoelectrochemical cell, and integrated nanosystem.